The relationship between FSH receptor polymorphism status and IVF cycle outcome: a retrospective observational study. Issue 2 (August 2019) - König, Tamar Elisabeth; van der Lee, Jessie; Schats, Roel; Lambalk, Cornelis Bavo
Highlights: FSH receptor gene polymorphism at position 680 is associated with a different ovarian response The Ser/Ser genotype is associated with a reduced ovarian stimulation outcome in IVF/ICSI The Asn/Asn genotype showed a significantly lower live birth rate Logistic regression showed no difference in cumulative live birth rate between the 3 genotypes Abstract: Research question: What is the association between FSH receptor ( FSHR ) gene polymorphism at position 680 and live birth in women undergoing IVF and intracytoplasmic sperm injection (ICSI). Design: In this retrospective cohort study, data were collected from the Electronic Patient Database of the VU University Medical Centre, Amsterdam, The Netherlands. Women undergoing their first IVF/ICSI cycle between January 2008 and March 2012, of whom the FSHR genotype was determined, were included. The main outcome was live birth rate. Secondary outcomes were ongoing pregnancy, total number of follicles, oocytes and embryos. Results: The FSHR genotype distribution was as follows: 334 women in the Asn/Asn group (28.2%), 617 in the Asn/Ser group (52.1%) and 234 in the Ser/Ser group (19.7%). Basal FSH concentration was highest in the Ser/Ser group ( P  = 0.006). The number of oocytes ( P  = 0.01) and number of embryos ( P  = 0.02) were lowest in the Ser/Ser group. The Asn/Asn group showed a significantly lower live birth rate. Live birth rates were 21.9% versus 31.1% and 27.6% ( P  = 0.009), for Asn/Asn, Asn/Ser and Ser/Ser, respectively. Logistic regression analysis, however, showed no significant difference on cumulative live birth rate between the three genotypes either unadjusted or when adjusted for age. Conclusion: The homozygous Ser/Ser genotype of FSHR polymorphism at position 680 is associated with a reduced ovarian response to ovarian stimulation in IVF/ICSI. No difference in cumulative live birth rate was found.